2020
DOI: 10.1149/1945-7111/ab8979
|View full text |Cite
|
Sign up to set email alerts
|

New, Dual-Anion Mechanism for Molten Carbonate Fuel Cells Working as Carbon Capture Devices

Abstract: Molten Carbonate Fuel Cells (MCFCs) are commercially employed in MW-scale power production, and recently are being developed also for carbon capture. Past experiments showed that MCFC performance with wet cathode feeding was higher than with dry cathode feeds at otherwise similar conditions. This was ascribed to a mechanism that predicted the water increasing the apparent CO 2 diffusion rate. However, recent tests performed at low CO 2 cathode feed concentrations, as in carbon capture service, showed the emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 52 publications
(67 reference statements)
2
31
0
Order By: Relevance
“…In previous studies (Audasso et al, 2020a;Audasso et al, 2020b;Rosen et al, 2020) we had not directly observed the presence of OH − ions in the electrolyte melt. We developed the dual-anion model construct based on global mass balances that indicated the cathode-anode migration of not only CO 2 , but also that of H 2 O.…”
Section: Melt Compositionmentioning
confidence: 75%
See 2 more Smart Citations
“…In previous studies (Audasso et al, 2020a;Audasso et al, 2020b;Rosen et al, 2020) we had not directly observed the presence of OH − ions in the electrolyte melt. We developed the dual-anion model construct based on global mass balances that indicated the cathode-anode migration of not only CO 2 , but also that of H 2 O.…”
Section: Melt Compositionmentioning
confidence: 75%
“…Experimental data also showed that the branching ratio between the two anion paths is determined by the reacting cathode gas composition (Rosen et al, 2020) and that, to favor the carbonate path, it is necessary to enhance CO 2 diffusion (Rosen et al, 2020;Audasso et al, 2020b). We have defined this simultaneous migration of carbonate and hydroxide ions as a "dual-anion" mechanism (Audasso et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the presence of molten hydroxides is likely in molten carbonates due to the presence of water, it is only until recently that their significant role has been demonstrated in the literature. Indeed, new studies show that these ions also contribute to overall MCFC performance in some conditions (Audasso et al, 2020;Rosen et al, 2020). For CO 2 -lean wet atmospheres, very high current densities, and/or high CO 2 usage, the MCFC can also operate using hydroxide as charge carrier, along with carbonates.…”
Section: Hydroxide Interference In Mcfcmentioning
confidence: 99%
“…Figure 5 recapitulates the reactions taking place at both anode and cathode side for both possible charge carriers. Audasso et al (2020) then proposed a dual-anion model to more accurately describe MCFC performance. In FIGURE 4 | Plots of measured CO 2 utilization rate versus expected, for various current densities, water contents, and CO 2 contents (Rosen et al, 2020).…”
Section: Hydroxide Interference In Mcfcmentioning
confidence: 99%